Private equity investment committee paper on biotelemetry, inc. – investment thesis and industry overview - Suppanz, Johannes (2020)
This Work Project was prepared in atea moffinance students and represents asimulated Private Equity Investment Committee Paper for aleverage buy out ofthe telemedicine company Bio Telemetry ,the US marked leaderin the field of remote cardiac monitoring and aprovide of glucose monitoring solutions as well as centralized research services for clinical trials. The leverage buy outconsists of comprehensive market and company analysis in cluding thorough valuation methods and the optimal financing structure, whichled to promising value creation strategies and respective returns cenarios. Fora successful exit, several options wereanalyzed, and recommendations made.